ANALISIS RASIO KEUANGAN DAN PENDEKATAN DISKRIMINAN Z-SCORE UNTUK MEMPREDIKSI TINGKAT KEBANGKRUTAN PT BUMI RESOUCES TBK - Riris Indah Sayekti (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2013)
This research focuses on the title of financial ratio analysis and Altman Z-Score disciminant approach to predict the level of PT Bumi Resources Tbk Bankruptcy. The aimof this research was to know to the financial performance of PT Bumi Resources Tbk on 2007-2011and to find out whether PT Bumi Resources Tbk included into the category of bankruptcy. This research using financial ratio wich consist of likuidity, profitability, solvability, activity and altman Z-Score discriminant approach.The results showed that by using financial ratios, PT Bumi Resources Tbk has weakness in the cash ratio which the amount of available cash is not sufficient to fulfill the companyy’s current liabilities. The analysis of net profit margin ratio does not indicate that the sales can produce a large amount of net profit for the company. PT Bumi Resources Tbk is not able to produce a rate return on investment and equity, it can be seen from the decrease of ROI and ROE. The dependence for the use of debt becomes bigger and makes overall solvency of company weak. The Altman Z-Score analysis shows that almost in every year the company in the position that has a great tendency on the verge of bankruptcy, but on 2009 the company has a tendency to go bankrupt immediately.Key word : financial ratio, bankruptcy, altman z-score